1995
DOI: 10.1016/0014-5793(95)00004-s
|View full text |Cite
|
Sign up to set email alerts
|

Folding intermediates are involved in genetic diseases?

Abstract: Recent experimental data show that some human genetic diseases are due to mutations in proteins which influence their trafficking and lead to retaining of proteins in the endoplasmic reticulum or their unproper processing. In this paper a hypothesis is proposed that these mutations are connected with an incomplete protein folding, blocking it at the stage of the kinetic molten globule or even earlier. If so, the specific drugs against these diseases may be ligands and other factors which facilitate the correct… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
50
0

Year Published

1996
1996
2008
2008

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 77 publications
(51 citation statements)
references
References 30 publications
1
50
0
Order By: Relevance
“…Elegant studies by Endo and Schatz revealed that the strong negative potential at the membrane surface attracts protons from the bulk solution resulting in a local decrease in pH, which consequently promotes the partial unfolding of proteins (46). Studies by Bychkova and Ptitsyn (47) and Wilkinson and Mayer (48) suggest that the membrane surface has a low dielectric constant. The acidic pH and the low dielectric constant at the membrane surface are shown to produce a denaturing microenvironment at the membrane surface.…”
Section: Discussion Possible Physiological Relevance Of the Partiallymentioning
confidence: 99%
“…Elegant studies by Endo and Schatz revealed that the strong negative potential at the membrane surface attracts protons from the bulk solution resulting in a local decrease in pH, which consequently promotes the partial unfolding of proteins (46). Studies by Bychkova and Ptitsyn (47) and Wilkinson and Mayer (48) suggest that the membrane surface has a low dielectric constant. The acidic pH and the low dielectric constant at the membrane surface are shown to produce a denaturing microenvironment at the membrane surface.…”
Section: Discussion Possible Physiological Relevance Of the Partiallymentioning
confidence: 99%
“…Indeed, Yogalingam et al (16) recently demonstrated that mutations in NAGLU do indeed affect the stability and transiting of the enzyme through the secretory pathway. It is a well described phenomenon that many point mutations in proteins cause changes in folding that abolish proper trafficking (19,20). Ironically, in many cases, these physiologically disastrous mutations do not destroy the catalytic activity and may only cause slight folding anomalies (21).…”
Section: Insights Into Mps Iiibmentioning
confidence: 99%
“…It has been suggested (Bychkova & Ptitsyn, 1995) that the appearance of some genetic diseases can be due to the existence of protein mutations, which results in the termination of protein folding at the molten globule stage. The most intriguing in this assumption is that such diseases can be treated by means of "treatment" of non-native proteins with the use of drugs (Bychkova & Ptitsyn, 1995).…”
Section: Ligand-induced Mg -+ N Transition and Genetic Diseasesmentioning
confidence: 99%
“…The most intriguing in this assumption is that such diseases can be treated by means of "treatment" of non-native proteins with the use of drugs (Bychkova & Ptitsyn, 1995).…”
Section: Ligand-induced Mg -+ N Transition and Genetic Diseasesmentioning
confidence: 99%
See 1 more Smart Citation